Electrocatalytic CO2 Reduction on CuOx Nanocubes: Tracking the Evolution of Chemical State, Geometric Structure, and Catalytic Selectivity using Operando Spectroscopy. (13th August 2020) - Möller, Tim; Scholten, Fabian; Thanh, Trung Ngo; Sinev, Ilya; Timoshenko, Janis; Wang, Xingli; Jovanov, Zarko; Gliech, Manuel; Roldan Cuenya, Beatriz; Varela, Ana Sofia; Strasser, Peter
Abstract: The direct electrochemical conversion of carbon dioxide (CO2 ) into multi‐carbon (C2+ ) products still faces fundamental and technological challenges. While facet‐controlled and oxide‐derived Cu materials have been touted as promising catalysts, their stability has remained problematic and poorly understood. Herein we uncover changes in the chemical and morphological state of supported and unsupported Cu2 O nanocubes during operation in low‐current H‐Cells and in high‐current gas diffusion electrodes (GDEs) using neutral pH buffer conditions. While unsupported nanocubes achieved a sustained C2+ Faradaic efficiency of around 60 % for 40 h, the dispersion on a carbon support sharply shifted the selectivity pattern towards C1 products. Operando XAS and time‐resolved electron microscopy revealed the degradation of the cubic shape and, in the presence of a carbon support, the formation of small Cu‐seeds during the surprisingly slow reduction of bulk Cu2 O. The initially (100)‐rich facet structure has presumably no controlling role on the catalytic selectivity, whereas the oxide‐derived generation of under‐coordinated lattice defects, can support the high C2+ product yields. Abstract : Cu2 O cubes of nanometer‐sized dimensions allow the chemical and structural factors that control the selectivity of the CO2 reduction reaction (CO2 RR) to be traced. The Faradaic product efficiencies over time can be linked to changes in the chemical state at the surface and bulk and in the catalyst morphology for supported and unsupported nanocubes (S‐NC, U‐NC).